Madrasah Aliyah dan Sekolah Menengah Kejuruan dalam Persepktif Ekonomi Islam - Nurhadi Nurhadi (PALAPA, 2021)
Formal Education Institutions that directly print productive age cadres are vocational madrasahs (MAK) and vocational high schools (SMK). The history and origins of MAK and SMK, that MAK is more oriented to religious education based on skills or skills as a means of living in the world. Whereas Vocational Schools almost certainly emphasize skills and skills. The contents of MAK's subjects are 70% religious subjects, 70% vocational subjects. Of the two MAK and SMK alumni who tend to study Islamic economics or courses in Islamic economics majors is MAK. Then MAK and SMK, if viewed from Islamic economic principles that are more directed at strengthening religious teachings, so that they can be practiced and applied in the world of work, according to the author MAK is more relevant and more profitable, both in the world and the hereafter. Especially if it is weighed by the theory of Islamic education and education philosophy that is oriented towards noble character and morality, the educational goals of Islamic economic perceptive MAK are closer to perfect compared to SMK